2004
DOI: 10.1002/hyp.1459
|View full text |Cite
|
Sign up to set email alerts
|

Snow accumulation in forests from ground and remote‐sensing data

Abstract: Abstract:Winter-forest processes affect global and local climates. The interception-sublimation fraction (F) of snowfall in forests is a substantial part of the winter water budget (up to 40%). Climate, weather-forecast and hydrological modellers incorporate increasingly realistic surface schemes into their models, and algorithms describing snow accumulation and snow-interception sublimation are now finding their way into these schemes. Spatially variable data for calibration and verification of wintertime dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 33 publications
(24 reference statements)
4
49
2
Order By: Relevance
“…The study area is covered by a coniferous forest, the canopy of which can efficiently intercept precipitation, especially in the form of snow. The intercepted rainwater or snow directly control water losses through sublimation governed by radiation fluxes [54,55]. Therefore, during a snow-melting period, forest decline or forest disturbance led to an increase in the frequency and magnitude of high flows [18,55].…”
Section: Discussionmentioning
confidence: 99%
“…The study area is covered by a coniferous forest, the canopy of which can efficiently intercept precipitation, especially in the form of snow. The intercepted rainwater or snow directly control water losses through sublimation governed by radiation fluxes [54,55]. Therefore, during a snow-melting period, forest decline or forest disturbance led to an increase in the frequency and magnitude of high flows [18,55].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SVF represents the weighted gap fraction from the forest floor (Hellstrom, 2000). Lundberg et al (2004) note that the use of SVF in analysing variability in snow distribution provides an accuracy comparable to other measurements of canopy density, such as leaf area index. A grey-scale threshold was used to discriminate between forest canopy and sky (Lundberg et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Others highlight the role of the forest canopy in controlling snow accumulation (through interception and subsequent evaporation/sublimation) and melting processes (by affecting various elements of the snow energy balance). Thus, spatial variations in the density of the forest canopy can lead to significant variations in the spatial distribution of snowpack, which in areas beneath a dense forest canopy can be as little as 40-50% of the snowpack thickness in open areas (Bernier and Swanson, 1992;Pomeroy and Gray, 1995;Pomeroy et al, 1998;Koivusalo and Kokkonen, 2002;Murray and Buttle, 2003;Lundberg et al, 2004). Recently, Talbot et al (2006) reported that snow dynamics are more highly dependent on stand density than on aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Truthful identification of the precipitation phase (rain/snow) is of course crucial for the functioning of meteorological models that forecast the precipitation phase itself [2] but also for accurate correction of gauge measured winter precipitation [3] and for land surface models (LSM) predicting snow accumulation and melt [4], glacier and polar ice water balance models [5], models for lake and sea ice growth [6], and climate change models [7]. It is also important for models predicting avalanche hazards [8], sublimation of snow in forests [9], urban snowmelt quality [10], winter road safety [11], infiltration into frozen soils [12], survival of mammals and plants under snow cover [13], flooding from rain on snow events [14] etc. Precipitation phase determination is a modeling challenge for both hydrology and meteorology; therefore, a cross discipline approach combining methods and knowledge from both sciences could lead to new insight for both.…”
Section: Introductionmentioning
confidence: 99%